Comparative analysis on definitions and types of apologies in apology legislation in the UK, Republic of Ireland, Australia, Canada, the USA and Hong Kong / Nurul Shuhada Suhaimi, Haswira Nor Mohamad Hashim and Noraiza Abdul Rahman - Suhaimi, Nurul Shuhada; Mohamad Hashim, Haswira Nor; Abdul Rahman, Noraiza (Universiti Teknologi MARA Cawangan Kedah, 2023)
This study compares the definitions and types of apologies adopted by apology legislation in selected Common Law jurisdictions i.e., England and Wales in the UK, Republic of Ireland, the states of New South Wales, Victoria and Queensland in Australia, Canada, the USA and Hong Kong. The apology legislative reform undertaken by these jurisdictions provides a solution to the long-standing problem of adverse legal effects of apology. A similar problem is reported in Malaysia due to similarities in evidentiary rules, insurance contract clauses and statutory limitation law attributed to the Common Law system. The objective of this paper is to comparatively analyses two scopes of the apology legislation, i.e., the definition and the type of apology adopted in the apology legislation by the selected Common Law jurisdictions. Based on the comparative analysis, this paper finds that there are three categories of the definition i.e., apology definition that includes acknowledgement of fault, apology which excludes acknowledgment of fault, and no definition of apology in the legislation. This paper also finds that there are two categories of types of apologies in the apology legislation in the analysed jurisdictions, i.e. full apology and partial apology. The findings of this paper help towards the development of the law that protects admission by apologetic discourse in Malaysia.